Transforming doctors' mess facilities to support clinician rest and wellbeing: a locally resourced initiative in an NHS hospital - Dominic Atraszkiewicz (British Journal of Healthcare Management, 2026)
Doctors commonly report poor work–life balance, sleep deprivation and inadequate rest and recuperation facilities at work. NHS doctors are typically required to fund and voluntarily manage their own common rooms, known as ‘doctors’ messes’. A three-phase project was undertaken to improve the management of a doctors’ mess at an NHS hospital in England. In phase one, five improvements were made to financial and procurement operations to increase annual cash flow by 85.5%. This allowed for a further 20 improvements to be made, in phase two, to the facilities and services in the mess. These included 24/7 provision of hot food, a coffee bar, sponsored lunches, social events, entertainment and personalised clothing. In phase three, the project was evaluated using a digital staff survey to measure satisfaction with the changes through both Likert-style and free-text questions. A follow-up survey was then conducted 1 year later to assess the sustainability of the changes made. In the first survey, 94.8% of staff scored the mess facilities with the highest satisfaction score of 5/5, with a mean score of 4.93/5.00. However, in the follow-up survey this had fallen to 2.04/5.00, with over one-third of respondents stating that none of the improvements had been maintained. This project demonstrates that meaningful changes can be made to doctors’ mess facilities to improve staff rest and wellbeing. However, it also highlights the need for continuity in management; ideally, doctors’ messes should be managed and funded by NHS leadership.